2019
DOI: 10.1111/fwb.13355
|View full text |Cite
|
Sign up to set email alerts
|

Net cages enhance golden mussel (Limnoperna fortunei) larval density and condition factor

Abstract: Cage fish farming is an important economic activity in Brazil where tilapia (Oreochromis niloticus) is the main cultivated species. To investigate the cage fish farm as a vector for golden mussel invasion, we hypothesised that: (1) Limnoperna fortunei, a freshwater bivalve mollusc, finds greater food availability in the cage fish farm; (2) the cage fish farm favours mollusc colonisation and its nutritional status; and (3) its performance in the reservoir would vary over the year. We obtained data from limnolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Boltovskoy and Cataldo (1999) found that mussels show accelerated growth during summer and reduced growth in winter, while Santos et al (2008) observed a greater growth of the golden mussel during the spring and summer. Furthermore, Rezende Ayroza et al (2019) confirmed that fish farming in net cages favors colonization and nutritional status of L. fortunei and its performance in the reservoir varies during the year in response to seasonality.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Boltovskoy and Cataldo (1999) found that mussels show accelerated growth during summer and reduced growth in winter, while Santos et al (2008) observed a greater growth of the golden mussel during the spring and summer. Furthermore, Rezende Ayroza et al (2019) confirmed that fish farming in net cages favors colonization and nutritional status of L. fortunei and its performance in the reservoir varies during the year in response to seasonality.…”
Section: Discussionmentioning
confidence: 82%
“…Pollution can originate from domestic sewage, garbage, agricultural and livestock waste, which can cause changes in water quality, eutrophication, and bioaccumulation of heavy metals, among others. The golden mussel can be a bioindicator that allows evaluating pollutions in the aquatic environment and the influence of the intensive system of fish in net cages in the environment since this cultivation system generates a supply of nutrients and minerals that can have negative effects on the existing fauna (Marengoni et al, 2013;Rezende Ayroza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, native communities and anthropic activities, such as hydroelectric and nuclear power plants (Boltovskoy et al, 2013;Cataldo et al, 2003;Darrigran et al, 2007) and fish farming in net cages in Brazil (De Rezende Ayroza et al, 2019), are affected. Limnoperna fortunei's fertilization is external, and its larval development is divided into two main stages: non-valvular, after fertilization until the formation of the trocophorous larva, and valvular, from veliger to plantigrade or pediveliger larva, when the planktonic phase ends.…”
mentioning
confidence: 99%
“…In the state of São Paulo, the third largest producer of Brazilian fish, Costa et al, (2018) calculated that the removal of mollusks fixed to the screens using a high-pressure device can lead to an increase of up to 27% in the cost of fish production. On the other hand, De Rezende-Ayroza et al, (2019) demonstrated that fish farming in cages favors the colonization of L. fortunei and ensures its nutritional status. They report that larval density and Condition Index in these areas were higher compared to control areas, particularly in the hottest period, because of higher concentrations of total phosphorus, nitrite, ammonium-N and chlorophyll a.…”
mentioning
confidence: 99%